Pengaruh Fee Audit, Audit Tenure, Dan Reputasi Kap Terhadap Kualitas Audit: - Hariani Novrilia; Fefri Indra Arza; Vita Fitria Sari (Jurnal Eksplorasi Akuntansi, 2019)
This research aims to determine the influence of audit fee, audit tenure, and audit reputation on audit quality. This type of research is causative research. The population and sample in this research are companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2017. The sample selection in this research used a purposive sampling method. Data type is secondary data. Data collection is done by collecting documentation data of financial statements of companies listed on the Stock Exchange for the 2015-2017. The data analysis method used is logistic regression analysis, with audit quality as the dependent variable and audit fee, audit tenure, and audit reputation as independent variables. The results of the research concluded that audit fee, audit tenure, and audit reputation does not have a significant relationship with audit quality.